A Bee Farm Records Management System: A Case Study of Kanyabugunga Kashambya Sub-County. - Maanige, Barnet; Tayebwa, Onesmas (Kabale University, 2024)
The Bee Farm Records Management System (BFMS) represents a pivotal advancement in supporting beekeepers in Uganda. Developed through an Agile Software Development Life Cycle, the web-based platform addresses key challenges in bee farming, including hive management, inventory control, and sales tracking. Designed for scalability, the system caters to beekeepers of varying scales, from hobbyists to commercial enterprises. The user-friendly interface encompasses features such as hive and inventory management, honey production tracking, and pest control. Leveraging technologies like MySQL, HTML, CSS, and PHP, the BFMS ensures efficient data storage, responsive web design, and dynamic functionality. User roles, including administrators and beekeepers, are defined to manage system access. Future avenues for enhancement include IoT integration for real-time hive monitoring, machine learning for pest detection, a dedicated mobile application, and expansion to other regions. User training, continuous feedback mechanisms, and sustainability assessments are recommended for ongoing system improvement. In conclusion, the BFMS has the potential to drive positive change in Uganda's beekeeping sector, contributing to economic development, environmental conservation, and food security. Success hinges on collaboration, user training, and responsiveness to evolving beekeeping needs. The system stands as a testament to the intersection of technology and agriculture, empowering beekeepers and fostering sustainable practices in bee farming.